Analysis of Factors Influencing Tensile Strength in Shielded Metal Arc Welding (SMAW) - Ginting, Canda Lesmana; Pranoto, Hadi (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2025)
Tensile strength in Shielded Metal Arc Welding (SMAW) is a critical parameter that significantly impacts the material's performance in mechanical structures. This welding method is widely used in various industrial applications, especially for carbon steel materials, due to its practicality and relatively low operational costs. This study aims to analyze the factors affecting tensile strength in SMAW welding, including welding current, electrode type and size, welding position, cooling medium, and welder skill. The analysis results show that increasing welding current can improve penetration and tensile strength, although it carries the risk of defects such as porosity and reduced weld quality. Selecting the right electrode, such as E7016, provides better tensile strength results compared to E7018, which excels in crack resistance. The horizontal welding position produces more consistent weld quality, while overhead position increases the risk of defects. Additionally, the cooling medium plays a significant role, with slow cooling using air or sand leading to a microstructure that supports better tensile strength compared to rapid cooling with water. Welder skill is also an important factor in controlling welding parameters to achieve optimal and strong welding results.